Ground penetrating radar imaging and its application to pavement structural assessment - Muslim, Nurul Hidayah (2014)
Traditionally, pavement distress evaluations were carried out by visual observation. In traditional practice, it requires a person to walk along the stretch of the pavement to conduct distress survey, take photo and measure defects occurred at deteriorated surface. However, this approach is too subjective, generates inconsistencies of information, less reliable and consumes lots of time. In lieu to this situation, some of the practitioners’ in pavement maintenance sector seek for other alternative tools and techniques to arrest incapability of traditional approach. One of the tools available in the market is Ground Penetrating Radar (GPR). GPR is a geophysical tool that is known with the ability to accommodate extensive data in pavement assessment, geotechnical investigation and structural assessment. The application of GPR is new to most of the practitioners in road maintenance industry in Malaysia. Therefore, this study has been undertaken to evaluate the benefits of using GPR in assessing pavement structure. The methodology for this study includes interviews with expert panels, followed by comparison of tools and GPR survey. The significant of tools comparison is to select the most appropriate tool for evaluation. Thus, GPR is compared with Infrared Thermograph (IR) and Portable Seismic Pavement Analyzer (PSPA) using the following parameters; cost-time effectiveness, operating principle, depth of performance, method of applications and limitations in order to select the most appropriate tool for further evaluations. Subsequently, GPR survey is being applied at a proposed location within UTM campus and findings are identified and processed using REFLEX 2D simulation software. The finding of this study concluded that GPR is highly advantageous over IR and PSPA for pavement structural assessments. GPR can perform at high speed and save time. It is also beneficial for long term investment due to numerous applications and vast ability to provide extensive information at a greater depth. There are three (3) types of information obtained from GPR survey such as; identification of raw image and processed image, identification of pavement segments thickness, and identification of GPR response towards surface and subsurface conditions which illustrated in radargram images. The interpretation of radargram images consumed more time due to the low resolution image captured by GPR. In view of this issue, selection of GPR system is crucial to ensure accuracy and clarity of radar images can be obtained nevertheless, all objectives in the study were achieved and verified